Constitutive model of semicrystalline polymer material. Implementation algorithm for mezolevel model - Nechaeva, Elena Sergeevna; Trusov, Petr Valentinovich (Computational Continuum Mechanics, 2011)
The authors present a constitutive model of a semicrystalline polymer material. To construct the model, a multilevel approach based on the use of internal variables in its structure - the parameters characterizing the state and evolution of meso- and microstructure of the material - has been applied. The model is based on the description of the main deformation mechanisms for this class of materials at the meso level: the shear along the crystallographic slip systems in lamellae, the interlamellar shear, the mechanism of spatial separation-compression for lamellae, and the quasi-rigid motion of the elements of each scale level. The general structure of the constitutive model of a representative volume for a semicrystalline polymer material and the algorithm of the model realization at the meso level are described.